2020
DOI: 10.1007/s10096-020-04033-0
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic and immunological characteristics of pregnant women with COVID-19 and their neonates

Abstract: Our aim was to investigate whether SARS-CoV-2 infection raised high risks of late pregnancy complications, and posed health problems in fetuses and neonates. We analyzed the data of COVID-19 pregnant women with COVID-19 during late pregnancy and their neonates. Eleven out of 16 (69%) pregnant women with COVID-19 had ++ or +++ of ketone body in urine. The blood uric acid of pregnant patients was 334 μmol/L (IQR, 269-452). D-dimer and FDP in pregnant patients were 3.32 mg/L (IQR, 2.18-4.21) and 9.6 mg/L (IQR, 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
2
18
1
3
Order By: Relevance
“…Hence, this common finding justified that viral infection could occur in several other anatomical regions besides the placenta since the newborn could be infected with SARS-CoV-2 through the umbilical cord, nasopharynx, maternal blood, amniotic fluid, and the vagina, which are all key regions involved during the birthing process ( Baud et al., 2020 ; Fenizia et al., 2020 ; Hosier et al., 2020 ; Pulinx et al., 2020 ; Vivanti et al., 2020b ; Zamaniyan et al., 2020 ). This study also found that there was an increased proportion of leukocytes, neutrophils, and lymphocytes in the newborn against SARS-CoV-2 indicating increased immune response activity against the virus ( Dong et al., 2020 ; Golden and Simmons, 2020 ; Vivanti et al., 2020b ; Zhou et al., 2021 ). However, it should be noted that in the small number of cases in which newborns progressed to severe SARS-CoV-2 infection, it was highly likely that these newborns were immunocompromised through an underlying condition, but since several existing pieces of literature did not account for this detail, further research is necessary to determine if specific underlying conditions amongst newborns could truly lead to an increased chance for severe COVID-19 and eventual death.…”
Section: Implications Of Sars-cov-2 Vertical Transmission On Developing Fetus or Newbornsupporting
confidence: 60%
See 2 more Smart Citations
“…Hence, this common finding justified that viral infection could occur in several other anatomical regions besides the placenta since the newborn could be infected with SARS-CoV-2 through the umbilical cord, nasopharynx, maternal blood, amniotic fluid, and the vagina, which are all key regions involved during the birthing process ( Baud et al., 2020 ; Fenizia et al., 2020 ; Hosier et al., 2020 ; Pulinx et al., 2020 ; Vivanti et al., 2020b ; Zamaniyan et al., 2020 ). This study also found that there was an increased proportion of leukocytes, neutrophils, and lymphocytes in the newborn against SARS-CoV-2 indicating increased immune response activity against the virus ( Dong et al., 2020 ; Golden and Simmons, 2020 ; Vivanti et al., 2020b ; Zhou et al., 2021 ). However, it should be noted that in the small number of cases in which newborns progressed to severe SARS-CoV-2 infection, it was highly likely that these newborns were immunocompromised through an underlying condition, but since several existing pieces of literature did not account for this detail, further research is necessary to determine if specific underlying conditions amongst newborns could truly lead to an increased chance for severe COVID-19 and eventual death.…”
Section: Implications Of Sars-cov-2 Vertical Transmission On Developing Fetus or Newbornsupporting
confidence: 60%
“…Furthermore, significantly varied levels of inflammatory biomarker CRP was observed in SARS-CoV-2 affected pregnant as well as postpartum women, inflammation caused by SARS-CoV-2 which may contribute for preterm birth ( Khalil et al., 2020 ; Woodworth et al., 2020 ). Along with the elevated levels of CRP, increased amounts of D-dimer have also been observed in infected pregnant women ( Areia and Mota-Pinto, 2020 ; Zhou et al., 2021 ), and research suggested that elevated levels of D-dimer may have led to the progression of COVID-19 disease severity in several pregnant women since high amounts of D-dimer signified an increased chance of acquiring Acute Respiratory Distress Syndrome (ARDS) and being admitted into the ICU and dying ( Vidali et al., 2020 ). A recent study has demonstrated the significant impact of COVID-19 infection on cytokine profile of pregnant women and that the cytokine levels being correlating with the severity of disease ( Tanacan et al., 2020 ).…”
Section: Immunopathogenesis Of Sars-cov-2 Infection In Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pre-existing heart disease had an 8-fold mortality rate and almost 3.5-fold need for admission to the ICU [ 32 ]. In other studies, the data of Covid-19 pregnant women with Covid-19 during late pregnancy and their neonates were examined [ 33 ]. Covid-19 enhanced placenta inflammatory responses, and possible organ dysregulation and coagulation disorders were observed in fetuses and neonates.…”
Section: Risk Factors Associatedmentioning
confidence: 99%
“…However, there have also been some reports where IgM were detected in the fetus. These include case reports and small studies from China [2 preterm ( Dong et al, 2020 ; Wu et al, 2020d ), 1 term ( Zhou et al, 2020 ), 2 term, 10 term ( Gao J. et al, 2020 ), 2 preterm-1 term ( He et al, 2020 )], the United States [one term ( Edlow et al, 2020 )], Italy [one preterm ( Fenizia et al, 2020 ), one term ( Cavaliere et al, 2020 )], and Sweden (three term Herlenius et al at Karolinska University Hospital, Stockholm, in progress) that also exhibited IgG against SARS-CoV-2 nucleocapsid and S-protein antibodies 0–2 days after birth.…”
Section: Sars–coronavirus 2 In Pregnancymentioning
confidence: 99%